2012
DOI: 10.1021/la302195m
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of High Pressure Methane Adsorption in Porous Aromatic Frameworks (PAFs)

Abstract: The adsorption isotherms of methane in four micro- and mesoporous materials, based on the diamond structure with (poly)phenyl chains inserted in all the C-C bonds, have been simulated with Grand Canonical Monte Carlo technique. The pressure range was extended above 250 bar and the isotherms were computed at 298, 313, and 353 K, to explore the potentiality of these materials for automotive applications, increasing the capacity of high-pressure tanks or storing a comparable amount of gas at much lower pressure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(73 reference statements)
2
24
0
Order By: Relevance
“…Since then, GCMC has been employed to predict CH4 adsorption isotherms in a wide range of MOFs and related structures [14,15,16,17,18,19,20,21,22,23], with reasonable agreement with experiment reported in many cases.…”
Section: Introductionmentioning
confidence: 68%
“…Since then, GCMC has been employed to predict CH4 adsorption isotherms in a wide range of MOFs and related structures [14,15,16,17,18,19,20,21,22,23], with reasonable agreement with experiment reported in many cases.…”
Section: Introductionmentioning
confidence: 68%
“…This model, referred to as mPAF-FCL, was easily prepared starting from the periodic structure of PAF-301, 30,36,53 i. e. a diamond network with a phenyl ring inserted in each CC bond: every two tetracoordinated carbons, two phenyl rings were replaced by hydrogen atoms as illustrated in Figure 2, and the structure was optimized by CRYSTAL09 with periodic boundary conditions. The resulting solid is far denser than the laboratory sample (0.87 instead of 0.53 g/cm 3 ), showing that the model crosslinking is excessive.…”
Section: B Crystalline-like Modelmentioning
confidence: 99%
“…HCP-11 is thermally stable up to 520 C in air and its absolute H 2 uptake can reach 10.7 wt% at 48 bar and 77 K, 127 its CO 2 uptake is 1300 mg g À1 at 40 bar and room temperature. 128 A theoretical simulation of high pressure methane adsorption of HCP-11 predicted a total methane uptake as high as 728 mg g À1 at 53.8 bar at 298 K. 129 Comotti studied the in situ solid-state polymerization of acrylonitrile in the cavities of HCP-11, proving that conned polymerization in porous frameworks leads to innovative nanostructured materials. 130 Zhou showed that post-functionalization of HCP-11 leads to enhanced properties.…”
Section: Hcp Generation Through Carbon-carbon Bond Formationmentioning
confidence: 99%